Neurobiological Evidence of Attentional Bias in Obsessive-Compulsive Disorder: Systematic Review - Ribeiro, Samara dos Santos (2021)
The attentional bias is the allocation of attentional resources to irrelevant stimuli during a task. It is assumed that patients with obsessive-compulsive disorder (OCD) presents attentional bias toward threatening stimuli. In order to describe OCD’s neurobiological findings of attentional bias towards a threat, it was performed a systematic review of experimental studies with neurobiological assessment in the following databases: MEDLINE, Web of Science, Scopus and LILACS. Four studies with control group are described in this review, all presenting statistically significant differences in brain activity associated with attention in patients. The neurobiological findings of the studies included in the review suggest allocation of attentional resources to irrelevant stimuli, regardless of the emotional valence in OCD.